The ‘Operational’ Definition of Self-Control - Gillebaart, Marleen (Frontiers in Psychology, 2018)
Self-control is a hot topic across disciplines. As such, consensus on defining self-control is critical for advancing both scientific progress as well as societal impact of research findings. Specifically, the emergence of initiation as a self-control component, and the notion of effortless and strategic self-control, give rise to the question whether and how to distinguish self-control from self-regulation. In this paper, I propose an operational definition of self-control, based on converging definitions from the literature as well as on the emergence of new perspectives on self-control. The TOTE-model (Test-Operate-Test-Exit) of self-regulation will serve as a basis for this definition as it gives clear guidance for the inclusion of self-control as a component of, but not synonymous to self-regulation. Ultimately, an ‘operational’ definition is proposed in which self-regulation entails scaffolding for goal pursuit, including setting standards, and monitoring discrepancies, whereas self-control entails everything that one does in the ‘operate’ phase. This perspective allows for inclusion of traditional as well as contemporary research on self-control, and can provide direction for future studies.